This body's not big enough for both of us : a novel - Cantero, Edgar, 1981- (Doubleday, 2018)
"From the New York Times bestselling author of Meddling Kids comes a brilliantly subversive and comic thriller celebrating noir detectives, Die Hard, Fast & Furious, and the worst case of sibling rivalry. You'll find their names on the frosted glass of a dingy office in Fisherman's Wharf. Adrian and Zooey Kimrean. Private Eyes. A.Z., as they are collectively known, are twin brother and sister. He's pure misanthropic logic, she's sloppy hedonistic creativity. He's Sherlock Holmes, the Cumberbatch version. She's Ace Ventura. A.Z. have been locked in mortal battle since they were in utero...which is tricky because they, very literally, share one single body. Still with me? One body, two pilots. The mystery and absurdity of how Kimrean functions, and how they subvert every plotline, twist, explosion, and gunshot--and confuse every cop, neckless thug, cartel boss, ninja, and femme fatale--in the book is pure Cantero magic. Someone is murdering the sons of the ruthless drug cartel boss known as the Lyon in the biggest baddest town in California--San Carnal. The notorious A.Z. Kimrean must go to the sin-soaked, palm-tree-lined streets of San Carnal, infiltrate the Lyon's inner circle, and find out who is targeting his heirs, and while they are at it, rescue an undercover cop in too deep, deal with a plucky young stowaway, and stop a major gang war from engulfing California. They'll face every plot device and break every rule Elmore Leonard wrote before they can crack the case, if they don't kill each other (themselves) first. This Body's Not Big Enough for Both of Us is a mind-blowing, gender-bending, genre-smashing romp through the entire pantheon of action and noir. Bad Boys II meets Hannah-Barbara meets Rick and Morty...it can only be Edgar Cantero"--